The regulatory journey to improving mine closure success in Western Australia - Risbey, D. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
Western Australia (WA) has a long and prosperous history in mining. The nature of mining requires some regulatory flexibility as many variables influence the life and economics of a project. Innovations in mining technology can turn a suspended mine into a viable one. Many mines continue beyond the initial forecasted mine life and may even be transformed to another post mining land use rather than rehabilitated back to native ecosystem. Some mines may even be ‘recycled’ enabling today’s waste to be used as tomorrow’s resource. Add to the mix community’s expectations for mined land to be rehabilitated and made safe, and the regulators of mine rehabilitation have a challenging conundrum. The Department of Energy, Mines, Industry Regulation and Safety (DEMIRS) aims for responsible development of resources and is the lead agency for mine closure in WA. The requirement for mine closure plans was introduced to the Mining Act 1978 in 2010 and led to the publication of ‘Guidelines for Preparing Mine Closure Plans’ in 2011 which drew national and international attention (DMP 2011). Hundreds of Mine Closure Plans (MCPs) later, mine closure planning is more mature with improved stakeholder engagement, research to close knowledge gaps and development of completion criteria. However, there has not been a noticeable increase in successfully closed mines being presented to government for relinquishment. This is despite there being many inactive mines with no exploration activity and appearing they would be better closed with post mining land use(s) enabled. Perhaps the process to seek relinquishment is not well understood? In an effort to demystify the process for seeking relinquishment under the Mining Act (i.e. formal acceptance from DEMIRS that rehabilitation and closure objectives under the Mining Act have been met), DEMIRS published the Mine Closure Completion Guideline in November 2021 (DMIRS 2021). Some companies have followed this guideline and received formal acceptance for parts of their mined areas, however progression towards successful closure still remains an elusive and sometimes half-hearted goal for many mines. The Mine Closure team at DEMIRS is undertaking a body of work in an effort to further the journey to improve the regulation of mine closure to enhance mine closure outcomes in WA. This work will explore ways to highlight the benefits of successful mine closure and that deferral of progressive rehabilitation and closure through prolonged periods of unjustified suspension of operations (care and maintenance) is a less attractive option. DEMIRS is working with other state government agencies with a regulatory role in mine closure to establish alignment in understanding what acceptable residual risk looks like for closed mines in WA. Other projects are planned by DEMIRS to improve timely regulatory intervention when poor closure practices are identified. DEMIRS looks forward to engaging with stakeholders as these continuous improvement projects progress and future initiatives developed to continually improve assurance that resources are mined responsibly in WA.